2011
DOI: 10.1371/journal.pbio.1001025
|View full text |Cite
|
Sign up to set email alerts
|

Local Ca2+ Entry Via Orai1 Regulates Plasma Membrane Recruitment of TRPC1 and Controls Cytosolic Ca2+ Signals Required for Specific Cell Functions

Abstract: Store-operated Ca2+ entry (SOCE) has been associated with two types of channels: CRAC channels that require Orai1 and STIM1 and SOC channels that involve TRPC1, Orai1, and STIM1. While TRPC1 significantly contributes to SOCE and SOC channel activity, abrogation of Orai1 function eliminates SOCE and activation of TRPC1. The critical role of Orai1 in activation of TRPC1-SOC channels following Ca2+ store depletion has not yet been established. Herein we report that TRPC1 and Orai1 are components of distinct chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
257
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(278 citation statements)
references
References 66 publications
14
257
2
Order By: Relevance
“…Conversely, TRPC1 silencing nearly abolishes outward I SOC , but it also reduces significantly the extent of the inward component. Consistently, it has been shown that STIM1 may drive interactions between ORAI1 and TRPC1 (39,50).…”
Section: Discussionmentioning
confidence: 56%
“…Conversely, TRPC1 silencing nearly abolishes outward I SOC , but it also reduces significantly the extent of the inward component. Consistently, it has been shown that STIM1 may drive interactions between ORAI1 and TRPC1 (39,50).…”
Section: Discussionmentioning
confidence: 56%
“…A complex pathway which interprets these intracellular Review Trends in Neurosciences August 2014, Vol. 37,No. 8 Ca 2+ signals to determine attraction or repulsion has been described [45,47], together with a recent model which represents this pathway mathematically [42].…”
Section: Discussionmentioning
confidence: 99%
“…When ER stores are depleted, the ER-resident stromal interaction molecule 1 (STIM1) localizes to the ER and plasma membrane junctions [31][32][33]. From here, STIM1 facilitates SOCE [34] through store-operated calcium (SOC) channels which utilize transient receptor potential cation (TRPC) channels and ORAI1, and calcium release-activated calcium (CRAC) channels which depend primarily on ORAI1 [33,[35][36][37]. Importantly, STIM1 localization in response to gradients of guidance cues is biased towards the up-gradient side of the growth cone, facilitating propagation of asymmetric Ca 2+ elevations [33].…”
Section: Glossarymentioning
confidence: 99%
“…In addition to InsP 3 R subtype specificity, maintenance of Ca 2+ oscillations is shown to require SOCe (25,32). SOCe requires STIM1, the ER luminal Ca 2+ sensor, which, upon Ca 2+ store depletion, translocates into ER/plasma membrane junctions and couples to activate Orai1 (50) and possibly transient receptor potential channels (TRPCs) (51,52). However, we recently revealed that STIM1 can act independently of ER Ca 2+ as a ROS sensor to induce Ca 2+ entry (14).…”
Section: Store-operated Camentioning
confidence: 99%